Simulation of intelligent sensors dipping into the melting polymer composite - Івіцький, Ігор Ігорович; Сокольський, Олександр Леонідович; Куриленко, Валерій Миколайович (Technology audit and production reserves, 2016)
One of the most important parameters of the finished product for intelligent sensors dipping into the melting polymer composite is the dipping depth of the sensors. Indeed, under the control of stress-strain state and other parameters using the sensor it is important to correlate obtained data with the sensor location – namely, the depth of its dipping for continuous product. In this regard, it is important for production to achieve accurate dipping of intelligent sensors at a given depth of the finished product, as, for example, stress measurement error for bending is directly proportional to the level of accuracy of the sensor dipping depth. The depth can vary from zero to mid-thickness of the product. Dipping simulation of intelligent sensors in the flow of the polymer material is carried out on the basis of the finite element method. Stationary problem is solved in the isothermal approximation. The basis is a generalized Newtonian flow model based on the continuity equation solution of incompressible fluid and momentum conservation. The study allows to reveal the required pressure ratio in primary and secondary channel with the dipping of intelligent sensors to the desired depth into the melting polymer material. An appropriate size of the finite element, material properties and boundary conditions for calculation are determined. Also the optimum angle of sensor dipping, which is 25°, and empirical equations of pressure ratio impact into additional and main channel to a depth of sensor dipping using approximations of dependencies obtained by numerical simulation are determined.